Cuerpo y vivencia : un encuentro consigo mismo. Un acercamiento desde la biodanza (2004)
ABSTRACT: The article indicates the existing relation among music, experience and movement, a triad that allows to extend the perspective of self-knowledge in people who regularly practice biodance, generating diverse pedagogies for life and enabling an encounter with oneself, with the others and with the surroundings. Starting with the self relation of the biodance system, ir is found that selfknowledge is associated with the internal connection of the body, corporal harmony, internal change, encounter with oneself, liberation of emotions, self expression and transformations in the way one feels and thinks.